2014
DOI: 10.1590/0102-311x00051313
|View full text |Cite
|
Sign up to set email alerts
|

Social geography of AIDS in Brazil: identifying patterns of regional inequalities

Abstract: The trend towards decline and stabilization of the AIDS epidemic in Brazil should be analyzed carefully, since aggregate data can mask regional or local inequalities in such a large and diverse country. The current study reevaluates the epidemic’s spatial dissemination and the AIDS-related mortality pattern in Brazil. The study considered all AIDS cases diagnosed in individuals over 18 years of age and living in Brazil, as well as AIDS deaths recorded in 1998-2008. Three-year moving average rates were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
0
27
0
5
Order By: Relevance
“…Apart from the last, the first five states have moderate population density and economic growth and, even expecting to have better Public Health conditions, they still have some latent risk factors for HIV/AIDS issue. As reported by Teixeira et al [44], AIDS epidemic in Brazil was only found to be expanding in the North and Northeast regions, while declining in the rest of the country, especially in the Southeast. Similar maps for models XXIV and XIV can be found on SuppMat Figure 3 and Figure 4, respectively.…”
Section: Model Selectionmentioning
confidence: 57%
“…Apart from the last, the first five states have moderate population density and economic growth and, even expecting to have better Public Health conditions, they still have some latent risk factors for HIV/AIDS issue. As reported by Teixeira et al [44], AIDS epidemic in Brazil was only found to be expanding in the North and Northeast regions, while declining in the rest of the country, especially in the Southeast. Similar maps for models XXIV and XIV can be found on SuppMat Figure 3 and Figure 4, respectively.…”
Section: Model Selectionmentioning
confidence: 57%
“…The presence of variables consid- Table 3 Joinpoint regression analysis of mortality rates related to TB-HIV/AIDS co-infection by region, sex and age group. ered indicators for poverty in Brazil and a higher risk among those with a low education and the black population, confirms the increased mortality in these regions 6,9,10,15,16,26,27 . Similar to other infectious diseases, poverty may have increased the vulnerability for TB and HIV/AIDS cases.…”
Section: Discussionmentioning
confidence: 73%
“…Similar to other infectious diseases, poverty may have increased the vulnerability for TB and HIV/AIDS cases. There is a clear link between TB, poverty and social exclusion, hampering control efforts in many Brazilian regions 10,27,28 . Those who are mostly affected live in poor, urban neighborhoods, with a trend to more and more rural areas 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to new infections in adults over 60 years, it can be inferred that a part of the AIDS cases and deaths in this age group may result from individuals being infected when they were aged 50-60 years, since the evolution time between HIV infection and AIDS diagnosis can be 5-10 years (Affeldt et al, 2015;Oliveira, Paz, & Melo, 2013). In this study, the highest AIDS-related mortality rates in people aged 60 years and older were observed in the most socioeconomically developed regions of the country, such as the South and Southeast (Girondi et al, 2012;Teixeira, Gracie, Malta, & Bastos, 2014). This is due to the fact that these regions recorded the most AIDS cases and present the highest incidence rates of the disease in the country (Brazilian Ministry of Health, 2015; Girondi et al, 2012).…”
Section: Discussionmentioning
confidence: 71%